Implementation of Menu Management at Kuta Puri Resort and Spa Kuta-Bali - Sukmana, IWK. Teja; Mertayasa, I Gede Agus; Eka Putra, Putu Steven; Sulistyo, Eko (Jurnal Manajemen Pelayanan Hotel, 2022)
This research is qualitative research to obtain a comprehensive portrait of the implementation of the menu management process in the restaurant operations of an independent three-star hotel. The study was conducted at Kuta Puri Bungalow Resort and Spa. The menu is the primary sales tool of any restaurant or culinary business to generate profit. Menu management is a sequential process consisting of menu planning, pricing, designing, operating, and development to achieve customer satisfaction and restaurant goals. Data were obtained from five respondents, of which three people are the key person in decision-makers at Restaurant Kuta Puri Bungalow Resort and Spa, the FB Manager, Chef de Party, and Restaurant and Bar Supervisor, and two-person is the crew level: a waitress and a Cook. Data were collected through interviews, observations, and documentation. The data is validated by source triangulation and method triangulation. The data was analyzed in qualitative analysis through four stages: data collection, data reduction, data presentation, and formulating conclusions. The results showed that in general, the management of Kuta Puri Resort and Spa had applied the dimensions of menu management in managing restaurants following the concept proposed by Ozdemir and Caliskan, (2014), Ozdemir and Nebioglu, (2018),Nebioglu (2020). But it differs in its operational variable i.e. menu layout and the presence of standard yield and butcher test. Keywords: Management, Menu, Restaurant,Hotel.